Complete subchondral bone defect regeneration with a tricalcium phosphate collagen implant and osteoinductive growth factors: A randomized controlled study in Göttingen minipigs. Issue 5 (21st November 2013) - Gotterbarm, Tobias; Breusch, Steffen J.; Jung, Martin; Streich, Nikolaus; Wiltfang, Jörg; Berardi Vilei, Simona; Richter, Wiltrud; Nitsche, Tobias
Abstract The restoration and reconstruction of osseous defects close to the joint, constitutes a challenging field for reconstructive surgery. A dual‐layer implant of β‐tricalcium phosphate (TCP) and a collagens I/III scaffold was evaluated in a prospective, randomized comparison in a larger animal model. For this purpose, a standardized osteochondral defect was created in the medial facet of the patellar groove in both stifle joints of Göttingen minipigs. Critical‐size osseous defects were either left empty (spontaneous healing; group 1; n = 12) or treated with the two‐layer TCP collagen implant (group 2; n = 12). In group 3 (n = 12), additional growth factor mixture (GFM) was supplemented (bone morphogenetic proteins 2, 3, 4, 6, 7, and TGF‐β1, 2, 3). Osseous defect regeneration was assessed at 6, 12, and 52 weeks postoperatively (n = 4). Qualitative and quantitative histomorphometric assessment of defect regeneration and bone substitute resorption was conducted by means of light microscopy, fluorescence microscopy, and microradiography. Critical‐size defects did not heal spontaneously throughout follow‐up (group 1: max. 21.84 ± 2.81% defect area at 52 weeks). The TCP layer of the implant significantly increased the amount of new bone formation with 29.8 ± 9.68% at 6 weeks and 40.09 ± 4.76% at 12 weeks when compared with controls. After 52 weeks, the TCP was almost fully degraded (4.35 ± 3.70%) and the defect was restored with lamellar trabecular bone (31.28 ± 5.02%). Growth factor supplementation resulted in earlier resorption of the TCP implant and faster defect regeneration. The dual‐layer TCP collagen implant is suitable to restore subchondral osseous defects. Additional use of GFM increased the resorption of the TCP layer, but did not foster new bone formation. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 933–942, 2014.